Representaciones existentes en torno a la infidelidad en diferentes tipologías de parejas heterosexuales no monógamas en jóvenes adultos (2022)
The aim of this research was to analyze existing representations of infidelity in young university students with non-monogamous heterosexual couples. This is due to the growing interest in nonmonogamous relationships in recent times, where recent studies show little prevalence of infidelity in this type of relationships and the concept that is faced with it. This study was developed under the phenomenological approach with exploratory scope. Therefore, the collaboration and participation of 4 persons of female and male sex, aged between 22 and 30 years, from different cities in Colombia, who have or had nonmonogamous relationships. The information obtained was through open interviews that were later analyzed by means of an analysis matrix that displayed the theoretical categories and the emerging ones that emerged from the interview.